How will Germany's CCS policy affect the development of a European CO2 transport infrastructure? - Christine Bertram; Nadine Heitmann; Daiju Narita; Markus Schwedeler (Kiel Institute for the World Economy (IfW), 2012)
CO2 storage opportunities and the location of coal-fired power plants are located far apart throughout Europe, suggesting the need for a region-wide CO2 pipeline network or at least a considerable number of cross-border transport pipelines. Regionally coherent policy would be needed to embed a CCS infrastructure into an evolving European electricity system. However, the current EU's CCS Directive leaves the decision to allow carbon storage on their territory to individual MSs and makes no provision for limiting local bans on CCS. Such EU policy should be reconsidered, as it could distort optimal pipeline infrastructure development and make pipeline construction more expensive. Germany, for example, is the largest emitter of CO2 in Europe, has the second largest storage capacities, and is located in the middle of Europe. A German ban on onshore storage of CO2 could not only unnecessarily increase the size of a transport network in Europe, but also the costs of building CCS infrastructure. It is worth stressing that the issue of building CCS infrastructure is a policy question that requires deliberation starting today, even if building most of the projects were likely to commence at least a decade later. Although CCS is not yet a fully established technology, steps should be taken now to set up a policy framework given the long time horizon that investment decisions in CCS infrastructure and power generation facilities would require. Moreover, the current uncertainty about the future of CCS also discourages private investment in CCS research and could thus hinder an even more efficient and effective use of this technology. As the present situation indicates, the implementation of CCS runs the risk of being deployed only in isolated cases, which would influence future energy mixes and might hamper the realization of stringent climate goals. Even if the use of renewable sources to produce energy increases in the future, coal will likely remain an important energy source for the next 20 years, particularly in Germany where nuclear power is to be phased out. In this context, CCS is a powerful option to reduce CO2 emissions to the atmosphere. Impeding the use of and research on CCS by not establishing appropriate regulations or even by prohibiting CO2 storage at this early stage, therefore, would pose the risk of losing one potentially important tool to combat climate change.
Keywords: 330; Kohlenstoffsenke; Kohlendioxid; Gasleitungstransport; EU-Staaten; Deutschland